Translation procedures applied in translating economic terms related to international trade = Phương thức dịch áp dụng trong dịch thuật ngữ kinh tế quốc tế - Phương, Minh Hằng (2021)
In the current context of globalization, international trade exerts great importance on the development of every economy. As a result, mutual understanding between international business partners must be enhanced in order to ensure the success of any business deal. Hence, translation of economic terms in business documents plays a significant role as a linguistic bridge between domestic enterprises and their oversea partners. In view of that, this study entitled “Translation Procedures Applied in Translating Economic Terms Related to International Trade” has been conducted with the purpose of investigating the procedures applied in translating international economic terms. First, the researcher aims at listing out the commonly-used translation procedures. In addition, this paper finds out the most dominant type of procedures applied in the translation of international trade terms. To achieve these objectives, the researcher collected and analyzed data from the text book “International Economics: Theory and Policy” (ninth edition) by Krugman Obstfeld Melitz and its translated version published by National Political Publishing House. Qualitative and quantitative analysis methods were employed to interpret the collected data. The results of this study suggested that among nine prominent translation procedures by Peter Newmark, through translation was the most frequently-used due to its accuracy. Following the common translation procedures, recommendations for appropriate translation procedures to deal with economic documents were also offered.